Revolutions at the frontline of multiple myeloma treatment: lessons and challenges to finding a cure - Kort, Jeries; Rivera, Andrea; Senigarapu, Sindhuja; Driscoll, James J. (Frontiers in Oncology, 2025)
Multiple myeloma (MM) is a cancer of bone marrow plasma cells. A noteworthy ensemble of therapies has been introduced over the past quarter century that exert antimyeloma activities through diverse mechanisms and achieve durable disease control in many patients. The discovery that proteasome inhibitors (PIs) and immunomodulatory drugs (IMiDs) target specific plasma cell features that reflect disease biology and exert antimyeloma activity led to transformative changes in treatment algorithms. Recently, advances in immunotherapy have emerged and represent a promising option with the potential to capture immunologic memory and yield more durable responses in MM patients. Idecabtagene vicleucel and ciltacabtagene autoleucel are chimeric antigen receptor (CAR) T-cell immunotherapies that attach to the extracellular domain of the B-cell maturation antigen (BCMA) and have demonstrated significant response rates in heavily-treated patients. These agents are FDA-approved for relapsed and/or refractory (RR)MM patients previously treated with PIs, IMiDs, and CD38-directed monoclonal antibodies. Most patients who receive CAR T-cell therapy relapse after prolonged or brief remission, and a more thorough understanding of the resistance mechanisms following CAR T-cell infusion is needed. Bispecific antibodies (BsAbs) are engineered to simultaneously bind to both cancer and immune cells and trigger a direct tumor-specific cytotoxic response. BsAbs and CAR T-cells are major histocompatibility complex (MHC)-independent approaches to treat MM and do not require T-cell receptor (TCR) specificity. Agents that target BCMA and G protein-coupled receptor class C group 5 member D (GPRC5D) demonstrate impressive clinical responses, while early-phase trials targeting FcRH5 are promising. Here, we provide a comprehensive overview of their individual efficacy, adverse effects, and limitations that impact broader application.